1998
DOI: 10.1159/000011918
|View full text |Cite
|
Sign up to set email alerts
|

Expression of p53 and Vascular Endothelial Growth Factor Associated with Tumor Angiogenesis and Prognosis in Gastric Cancer

Abstract: Recently, it has been reported that p53 tumor suppressor gene plays an important role in controlling tumor angiogenesis by regulating expression of vascular endothelial growth factor (VEGF), which is a well-characterized angiogenic inducer. In this study, we investigated these antigens’ expression together with microvessel density, and investigated their clinical importance. One hundred twenty specimens resected from patients with gastric carcinoma were investigated using immunohistochemical methods. p53 and V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
2
9

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 18 publications
7
55
2
9
Order By: Relevance
“…By contrast, other authors have not shown the association of p53 expression with node metastases or serosal invasion Maeda et al, 1998). Our study agrees with these latter results, since p53 expression did not correlate to a more advanced tumour stage.…”
Section: Discussionsupporting
confidence: 89%
“…By contrast, other authors have not shown the association of p53 expression with node metastases or serosal invasion Maeda et al, 1998). Our study agrees with these latter results, since p53 expression did not correlate to a more advanced tumour stage.…”
Section: Discussionsupporting
confidence: 89%
“…The direct correlation between p53 and VEGF in colon cancer has already been reported by Takahashy, who suggested that the p53 tumor suppressor gene influenced VEGF expression [37]. Some studies have also showed that aberrant p53 expression is associated with VEGF overexpression in human solid cancers, including colon cancer [38,39], gastric cancer [40] and NSCLC [41,42]. Famulski W. et al also demonstrated the positive correlation between serum levels of p53 and VEGF, and it has been suggested that this is a probable sign of a poor prognosis in colorectal cancer [43].…”
Section: Discussionmentioning
confidence: 67%
“…It has been shown that patients with VEGF-overexpressing gastric cancer have shorter tumor-free and overall survival [6,7,8, 14, 15,19,20,21,22,23]. In lymph node-positive resected gastric cancers, the presence of VEGF-D/VEGFR-3 has been shown to be associated with poor survival [24,25,26,27,28,29,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic significance of MVD in solid tumors including gastric cancer has been investigated in many studies [13]. Higher MVD scores were shown to be associated with poor outcome in gastric cancer [6,14,15,16]. …”
Section: Introductionmentioning
confidence: 99%